ChemInform Abstract: Sulfoximine Assisted Pd(II)‐Catalyzed Bromination and Chlorination of Primary β‐C(sp3)—H Bond. Issue 13 (March 2015) - Rit, Raja K.; Yadav, M. Ramu; Ghosh, Koushik; Shankar, Majji; Sahoo, Akhila K.
Abstract Novel MPyS‐directing‐group‐assisted bromination and chlorination of primary β‐C(sp3)—H bonds of aliphatic acid derivatives is demonstrated for the first time.